IMPACT OF SOFT POWER FACTORS ON EXCHANGE RATE VOLATILITY: EVIDENCE FROM SOUTH AND EAST ASIAN COUNTRIES - Bacha, Mehran; Wadood, Fazli; Akbar, Fazal (The journal of contemporary issues in business and government, 2021)
This paper aims to examine the impact of soft power factors on exchange rate volatility of South and East Asian countries. In past, very limited research work has been done regarding soft power factors and their relationship with exchange rate volatility in South and East Asian countries. This paper is an attempt to explore how soft power factors (including governance variables, population variables, education variables, financial variables, and economic growth variables) capturing countries influence components of exchange rate volatility. However, present paper has used monthly panel data set of nineteen South and East Asian countries during the period of 2007-2017, PCA index of soft power variables are constructed and common effect fixed effect panel data techniques are used for analysis. Exchange rate volatility is measured through Arch Garch. Results concluded that, population variables and financial variables have significant negative relationship with exchange rate volatility. Meanwhile, governance variable, education variables, and economic growth variables have insignificant relationship with exchange rate volatility. This paper will contribute in existing literature theoretically and also provides important policy implications for financial and public institutions.